Pre-participation medical evaluation in rink hockey players - de Pablo Marquez, Bernat; Peña, Javier; Grazioli, Gonzalo; Rodas, Gil; Casals, Martí (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The aim of this study was to describe the medical findings and the physical imbalances during pre-participation screenings among rink hockey players. A cross-sectional study was conducted on 773 rink hockey players (645 males and 128 females, 14 to 43 years old) from different teams participating in regional competitions. The pre-participation screening included: a) medical history, b) anthropometrical data, c) physical examination, d) baseline 12-lead ECG, and e) an extensive orthopedic evaluation. A total of 773 pre-participation evaluations were included. Anthropometry evaluation showed 20.2% were overweight and 4.1% classed as obese. The prevalence of previous injuries related to rink hockey was 24,4% (CI 95% 21.5-27.5). The lower limb was the most affected area, and fractures were the most frequent injuries. Four (0.05%) life-threatening cardiopathies were found and treated. Regarding musculoskeletal examination, 29 athletes (4%) presented spine alignment alterations, 69 (8.9%) presented lower leg dysmetria, and 150 (19.4%) feet misalignment. Pre-participation screening is essential in detecting medical conditions and physical imbalances affecting athletes’ health. These medical evaluations must be recommended for athletes of all levels.